Emotional Maturity in Adolescents with Physical Disabilities: The Impact of Parental Attachment - Nathania, Elizabeth Indah Dwi; Kusumiati, Ratriana Yuliastuti Endang (Jurnal Bimbingan dan Konseling Terapan, 2024)
Adolescents with physical disabilities also undergo a transitional period during adolescence, requiring assistance to achieve emotional maturity appropriate for their age. This necessitates support from the immediate environment, which can be obtained through parents. The aim of this study is to investigate the relationship between parental attachment and emotional maturity in adolescents with physical disabilities. The participants in this study were 56 adolescents with physical disabilities in the city of Salatiga, aged between 11 and 20 years. The sampling technique used in this study was snowball sampling. Data collection utilized the Inventory of Parent Attachment, consisting of sections on attachment to the mother and attachment to the father, and the second scale employed the Emotional Maturity Scale (EMS). The results of this study indicate a significant positive relationship between attachment to parents and emotional maturity, with a correlation of r = 0.452 and significance of 0.000 (p<0.05). This means that the higher the level of secure attachment to parents, the higher the emotional maturity in adolescents with physical disabilities. The findings of this study can be used to develop interventions for specialized educational institutions for individuals with disabilities and serve as a reference for readers.